HUBUNGAN LAMA PENGGUNAAN KB SUNTIK DMPA DENGAN KEJADIAN PENURUNAN LIBIDO: HUBUNGAN LAMA PENGGUNAAN KB SUNTIK DMPA DENGAN KEJADIAN PENURUNAN LIBIDO - Sri Hadi Sulistiyaningsih; Yuyun Ike Perdana (Jurnal Kebidanan, 2022)
Decreased sexual desire (libido) in DMPA injection contraceptive acceptors, although it is rare and not experienced by all women, but in long-term use it can arise due to hormonal changes, resulting in vaginal drying which causes pain during intercourse and ultimately reduces sexual desire or arousal. . The purpose of the study was to determine the relationship between duration of use of DMPA injectable contraception with the incidence of decreased libido at the Moswaren Health Center, Moswaren District, South Sorong Regency. The type of research is correlational analytic with the cross-sectional approach. The sample in this study was DMPA injection family planning acceptors as many as 50 respondents who were taken using random sampling technique and statistical analysis test using the Kendall Tau test. The results showed that the majority of respondents used DMPA injections for > 2 years as many as 23 people (46%), 22 respondents with a moderate decrease in libido (44%), and there was a relationship between the length of time using DMPA injections with decreased libido at the Moswaren Health Center. Moswaren District, South Sorong Regency, West Papua with p-value 0.000 <0.05. It is hoped that health workers can improve health education and counseling about various types of contraceptives and the possible side effects that will occur so that prospective family planning acceptors can make the right decisions in choosing contraceptives and accept the side effects they experience. Keywords: duration of use DPMA injection contraception, decreased libido